Triplebody Mediates Increased Anti-Leukemic Reactivity of IL-2 Activated Donor Natural Killer (NK) Cells and Impairs Viability of Their CD33-Expressing NK Subset - Kloess, Stephan; Ede Valverde da Silva, Alessa; Oberschmidt, Olaf; Gardlowski, Tanja; Matthies, Nadine; Vyas, Maulik; Arseniev, Lubomir; Heuser, Michael; Pogge von Strandmann, Elke; Köhl, Ulrike (Frontiers in Immunology, 2017)
Natural killer cells (NK) are essential for the elimination of resistant acute myeloid and lymphoblastic leukemia (AML, ALL) cells. NK cell-based immunotherapies have already successfully entered for clinical trials, but limitations due to immune escape mechanisms were identified. Therefore, we extended our established NK cell protocol by integration of the previously investigated powerful trispecific immunoligand ULBP2-aCD19-aCD33 (so called triplebodies, [TBs]) to improve the anti-leukemic specificity of activated NK cells. IL-2-driven expansion led to strongly elevated NKG2D expressions on donor NK cells which promote the binding to ULBP2+TBs. Similarly, CD33 expression on these NK cells could be detected. Dual-specific targeting and elimination were investigated against the B-cell precursor leukemia cell line BV-173 and patient blasts, which were positive for myeloid marker CD33 and B lymphoid marker CD19 exclusively presented on biphenotypic B/myeloid leukemia’s. Cytotoxicity assays demonstrated improved killing properties of NK cells pre-coated with TBs compared to untreated controls. Specific NKG2D blocking on those NK cells in response to TBs diminished this killing activity. On the contrary, the observed up-regulation of surface CD33 on about 28.0% of the NK cells decreased their viability in response to TBs during cytotoxic interaction of effector and target cells. Similar side effects were also detected against CD33+T- and CD19+B-cells. Very preliminary proof of principle results showed promising effects using NK cells and TBs against primary leukemic cells. In summary, we demonstrated a promising strategy for redirecting primary human NK cells in response to TBs against leukemia, which may lead to a future progress in NK cell-based immunotherapies.